(untitled) (Journal of Economic Research & Business Administration, 2015)
Abstract. Formation of open technological society in any way, directly or indirectly, affects the state and its citizens. Obviously, each country suffers from global crisis. Therefore, mankind is interested to work together to solve common problems of world development. Doubtless, no matter how powerful is the country, it can’t solve all the problems alone. All counties should work together to develop innovations and the global economy. This article considers the ways and methods of solving problems of aging technologies on a global scale, as well as subjects of international relations of the global economy. It is also says that the global integration of innovation and technology transfer contributed to the development of the relationship between developed and developing countries. Transfer of technology not only has a positive effect on development of a developing country, but also gives a powerful impetus to the economy. The article presents a comparative analysis of the domestic economy with foreign ones, and suggests ways to improve the innovative performance.